Bis(amino)cyclopropenylidene Catalyzed Rauhut–Currier Reaction between α,β-Unsaturated Carbonyl Compounds and para-Quinone Methides - Goswami, P.; Sharma, Sonam; Singh, Gurpreet; Anand, R.V. (American Chemical Society, 2018)
An intermolecular Rauhut–Currier reaction between α,β-unsaturated carbonyl compounds and p-quinone methides has been developed by employing bis(amino)cyclopropenylidene as a catalyst. This protocol allows access to a variety of vinyl diarylmethane derivatives in moderate to good yields.
Keywords: para-Quinone Methides; Bis(amino)cyclopropenylidene; Rauhut–Currier Reaction; Unsaturated Carbonyl Compounds